Utilization of Crude Glycerol Waste from Biodiesel Production as an Additive to Improve the Quality of Tea Dreg Biopellet - Lilis Sucahyo; Imelda Hellen ABR Sembiring; Dyah Wulandani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Biodiesel production using the transesterification method generates a large amount of crude glycerol as by-products. Crude glycerol waste can be reused and utilized as an additive in the formulation of biopellet. Tea dregs are a waste produced by the beverages industry that can be used as green fuel in the form of biopellet as an environmentally friendly energy source. This study aims to analyze and characterize biopellet from tea dregs with crude glycerol as an additive to increase the quality. The biopellet formulation contains six levels of crude glycerol composition percentage: 0% (as control), 5%, 10%, 15%, 20%, and 25%. The parameters for the quality assessment of biopellet refer to the SNI 8675:2018 standard. The best formulation of biopellet was obtained in the 10% treatment with properties of density value of 0.93 g/cm3, pellet durability of 98.09%, moisture content of 8.10%, volatile matter content of 73.37%, ash content of 6.08% and calorific value of 16.38 MJ/kg. The addition of up to 10% crude glycerol as an additive has been shown to improve the quality of tea dregs biopellet. Keywords:  Additive, Biopellet, Crude glycerol, Tea dregs.